Treatment of Intracranial Superfi cial Micro-AVMs: A Single Center Experience - GM Overdevest; AC van Es; MAA van Walderveen; PWA Willems (Journal of Neurology, Neurological Science and Disorders - Peertechz Publications, 2017)
Background: Surgery and embolization may both be considered in ruptured superficial micro-AVMs. However, surgery may be challenged by poor recognition of the lesion and embolization by difficulty in achieving complete obliteration and avoiding en passage feeders. Recent developments in AVM surgery and embolization techniques call for a reevaluation of these treatment options. Methods: Eight consecutive patients with superficial micro-AVMs are presented. All patients received an initial embolization attempt with either nBCA or ONYX. If complete obliteration was not obtained, either a second embolization or surgical resection was offered. At surgery, indocyanine green video angiography (ICG-VA) was used in all cases. Effectiveness and safety of all procedures were evaluated retrospectively. Functional outcome at 6 months was assessed by the modified Ranking Score (mRS). Results: Patients had a mean age of 52±17 years and all presented with hemorrhage. The mean nidus size was 4 mm, and was localized supratentorially in 5 cases and infratentorially in 3. Initial embolization was successful in 2 patients (25%). One patient underwent a second, unsuccessful, embolization attempt and 1 patient did not receive further treatment. Consequently, five patients underwent surgery, which was successful in four (80%). The unsuccessful case was successfully reoperated. The only two procedural complications were related to superselective embolization, but neither caused clinical sequelae. Mean clinical follow-up was 29 months (range, 4-75mo), with mRS 0 in 2, mRS 1 in 4 and mRS 3 in 2 cases. Conclusions: In a current case series, embolization of superficial micro-AVMs was associated with a lower success rate (25% vs 80%) than microsurgery and a higher procedural complication rate (minor complications: 22% vs 0%).